Daily Costs Strategy dalam Gadai Emas Di Bank Syariah Sarana Prima Mandiri Pamekasan - Wulandari, Susmita; Mansur (LP2M IAI Miftahul Ulum Pamekasan, 2024)
This study aims to describe the strategy carried out by the Islamic Bank PT. BPRS Sarana Prima Mandiri to attract customers. Interestingly, because the location of this private bank is close to a government bank. The method used in this research is descriptive qualitative. While the results of this study are that the strategy used is able to attract customers, especially in gold pawning financing, which costs much less than in SOE Pawnshops. Safekeeping fees are calculated per day (daily costs). This is a special attraction for customers, so that it becomes one of the superior products at the SPM Sharia Bank. While the product introduction technique is by distributing brochures and hospitality to customers' and prospective customers' homes.